2015
DOI: 10.1111/zoj.12281
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic position and composition of Zygiellinae andCaerostris, with new insight into orb-web evolution and gigantism

Abstract: Orb-weaving spiders are good objects for evolutionary research, but phylogenetic relationships among and within orb-weaving lineages are poorly understood. Here we present the first species-level molecular phylogeny that includes the enigmatic orb weavers 'Zygiellidae' and Caerostris. Zygiellidae is interesting for the evolution of the sector web, and Caerostris is noteworthy for web gigantism and extraordinary silk biomechanics. We assembled a molecular data set using mitochondrial (COI, 16S) and nuclear (H3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 92 publications
4
30
0
Order By: Relevance
“…This change in rank better reflects our improved understanding of the phylogenetic position and evolutionary history of nephilines while maintaining the diagnosability of Nephilinae, and avoids the paraphyly of Araneidae implied by several recent published studies (e.g. Kuntner et al., ; but see Gregorič et al., ) and by the Bayesian results of this study (Fig. S2).…”
Section: Taxonomysupporting
confidence: 75%
“…This change in rank better reflects our improved understanding of the phylogenetic position and evolutionary history of nephilines while maintaining the diagnosability of Nephilinae, and avoids the paraphyly of Araneidae implied by several recent published studies (e.g. Kuntner et al., ; but see Gregorič et al., ) and by the Bayesian results of this study (Fig. S2).…”
Section: Taxonomysupporting
confidence: 75%
“…For example, some species described from Australia most likely do not really belong to Araneus (see Framenau 2012). Moreover, recent studies based on analyses of species from North America, Europe, and Australia have shown that Araneus is polyphyletic (Gregoric et al 2015), which has been further corroborated by recent phylogenomic studies (Kallal et al 2018). …”
Section: Introductionsupporting
confidence: 53%
“…None of the suggested sister group relationships was well supported (e.g. Gregorič et al., ). Recent phylogenomic studies have placed Araneidae sister to Linyphiidae + Pimoidae and Nesticidae (Garrison et al., ), or to Theridiosomatidae (Fernández et al., ), but it is hard to compare the two studies.…”
Section: Introductionmentioning
confidence: 99%